Kualitas Air Sungai Konda, Kais, Metamani dan Inanwatan Kabupaten Sorong Selatan - Marhan Manaf; Suhemi (AquaMarine (Jurnal FPIK UNIDAYAN ), 2023)
This study aims to obtain information or an overview of the water quality status of the Kaibus river (Teminabuan river), Kais river, Metamani river, Musiro river, Rur river, Nurangge river, Kamamur river, Sepa river, Suaboor river, Awoge river, Sekak river, and the Siganoy river. The method of measuring water quality is carried out directly in the field (on-site) and consists of temperature, pH, DO, TDS, salinity, and brightness. Meanwhile, what cannot be done on-site, is carried out by taking composite samples to be observed in the laboratory (ex-situ). The results showed that the quality status of river water in the Konda District, Kais District, Metamani District, and Inanwatan District are classified as lightly polluted waters with a Pollution Index between 0.85 and 3.10. Water quality parameters contributing to the Pollution Index in the lightly polluted category are low DO values and high concentrations of BOD, COD, Boron, Fluoride, and Surfactants.